2018
DOI: 10.1515/eces-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation Effect of Selenium on Manganese Stress of Plants

Abstract: Mn, as Fe, Zn, Cu and Ni is a heavy metal and also a necessary element all the living organisms. Excessive Mn nutrition causes a strong oxidative stress. The aim of the studies was to determination the effect of Se treatment (as sodium selenite Na2O4Se3) to alleviate the Mn stress of plants. Because of its sensitivity to oxidative stress induced by excessive concentrations of Mn a model plant was lettuce (Lactuca sativa L. 'Sunny'). ). In all the combination were also tested different foliar sprays (distilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Manu) roots and flag leaves decreased when exposed to greater doses of Se (15 μm) in comparison to a lower application rate (5 μm Se) [ 56 ]. In the presence of S, Se foliar application may sustain the Mn accumulation in the spinach’s edible sections [ 57 ]. It has been noted that at high Se doses, Mn concentrations decreased in all plant organs, which might be attributed to the suppression of Mn uptake by roots.…”
Section: Discussionmentioning
confidence: 99%
“…Manu) roots and flag leaves decreased when exposed to greater doses of Se (15 μm) in comparison to a lower application rate (5 μm Se) [ 56 ]. In the presence of S, Se foliar application may sustain the Mn accumulation in the spinach’s edible sections [ 57 ]. It has been noted that at high Se doses, Mn concentrations decreased in all plant organs, which might be attributed to the suppression of Mn uptake by roots.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the mechanism of Se-based protection involves its blocking the uptake and transport of toxic substances (Koselski et al 2019) and/or reducing the overproduction of ROS (Sieprawska et al 2015;. Another mechanism may be a Se-mediated modification of the methylation pattern disturbed by stress factors (Filek et al 2008;Kleiber et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the mechanism of Se-based protection involves its blocking the uptake and transport of toxic substances [32] and/or reducing the overproduction of ROS [29,33]. Another mechanism may be a Se-mediated modification of the methylation pattern disturbed by stress factors [34,35].…”
Section: Introductionmentioning
confidence: 99%